2017
DOI: 10.1111/jocn.14096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different methods of reflection on nurses' gaze and judgement in a task using a touch panel

Abstract: Reflective writing promotes visual verification in nurses in a clinical setting while performing a task using a touch panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This situation is sometimes hindered by an increase in the number of students and by the lack of resources [15]. In order to improve this aspect, it is necessary to involve students in their learning process in an active manner, away from the passive attitude of master classes, and supported by oral and written reflection [16]. Debates, brainstorming, group discussions and open questions represent some of the interactive methods that can be included in the educational practice so as to promote learning [17].…”
Section: Introductionmentioning
confidence: 99%
“…This situation is sometimes hindered by an increase in the number of students and by the lack of resources [15]. In order to improve this aspect, it is necessary to involve students in their learning process in an active manner, away from the passive attitude of master classes, and supported by oral and written reflection [16]. Debates, brainstorming, group discussions and open questions represent some of the interactive methods that can be included in the educational practice so as to promote learning [17].…”
Section: Introductionmentioning
confidence: 99%
“…41 Furthermore, opportunities for adequate reflection improve clinical decision making, facilitate better understanding of patient situations, 42 and enhance the capacity to properly assess the requirements of diverse care situations. 43 That said, our results revealed that such organizational programs and associated opportunities are decidedly lacking in healthcare settings. Addressing this problem via the provision of such programs could be critical not only to improving the health of nurses and midwives but also to reducing turnover rates in accordance with the WHO's Sustainable Development Goals for 2030.…”
Section: Discussionmentioning
confidence: 76%
“…26,33,35 With technological advancements, two studies utilized different forms of electronic devices to assist in the reflective process. 36,37 These devices reinforced visual aid for nursing students on experiential placement.…”
Section: Reflective Practice In Healthcare Educationmentioning
confidence: 99%